Inverse association between blood ethylene oxide levels and obesity in the general population: NHANES 2013–2016 - Cheang, Iokfai; Zhu, Xu; Zhu, Qingqing; Li, Menghuan; Liao, Shengen; Zuo, Zhi; Yao, Wenming; Zhou, Yanli; Zhang, Haifeng; Li, Xinli (Frontiers in Endocrinology, 2022)
Background: Ethylene oxide (EO) has been shown to associate with increased cardiovascular risk. This study aimed to explore the relationship and its meditating factors between EO exposure and the major cardiovascular risk factor of obesity among the general adult population. Methods: Cross-sectional data of 3,220 participants from National Health and Nutritional Examination Survey (NHANES) 2013–2016 were enrolled. Obesity was defined body mass index (BMI) ≥30kg/m2, and abdominal obesity was waist circumference (WC) ≥102 cm in men and ≥88 cm in women. The association among hemoglobin adduct of EO (HbEO), inflammatory biomarkers, and obesity were evaluated using restricted cubic spline and multivariable linear regression model. Mediation analysis was used to further assess their association. Results: The increased quartiles of HbEO were inversely associated with BMI and WC [Q1 vs Q4, BMI: β=-2.98 (-3.74, -2.22), WC: β=-6.50 (-8.60, -4.39); all P for trend <0.05), and were inversely associated with obesity after full adjustment (Obesity: OR=0.43 (0.31, 0.58), Abdominal obesity: OR=0.42 (0.27, 0.65); all P for trend <0.05). The levels of alkaline phosphatase, white blood cells, lymphocytes, and neutrophils were also positively associated with BMI and WC (All P <0.05). Mediation analysis showed that exposure of EO not only had a negatively direct effect on BMI and WC, but also generated an inverse indirect effect. Conclusions: Current findings showed an inverse association between HbEO and obesity, and suggested that systemic inflammation may not be their only mediator. Additional research is required to explore the underlying link of EO and system metabolism.